The Ottoman Hammam Al-Ward In Saida, Lebanon - al-Harithy, Howayda (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2016)
Hammam Al-Ward is an Ottoman monument in Saida. Siada (or Sidon) is a coastal city in Lebanon and a hidden treasure with numerous Mamluk and Ottoman monuments. These monuments are of various types, from mosques to hammams to palaces and khans. They remain unstudied and at times undocumented. This is an architectural monograph of Hammam Al-Ward placed within the urban history of the city and the social practices of its inhabitants. Through documentation and comparative analysis, the paper argues that the hammam was built during the early eighteenth century but carries within it an old tradition of building that dates back to the Mamluk period and an old socio-spatial practice that dates back to Roman times. The article investigates and presents the urban condition that unfolds through the hammam patronage, style and location, the architectural interpretation of the hammam type of the Mediterranean Arab World and the socio-spatial practices of bathing and leisure that continue till modern times.